Die Verbraucherverbandsklage in Japan - Lentz, Maximilian (Zeitschrift für Japanisches Recht, 2009)
The article deals with the new action for an injunction by consumer associations under the Japanese Consumer Contract Law. It explains the requirements a consumer association has to fulfil to be for qualified for conducting services regarding actions of injunction. Basically, an injunction can be sought against misleading advertisements and unjust contract-clauses. It is demonstrated that various restrictions remain with regard to the possibility to file for an injunction. The article raises various issues discussed in connection with the reform, e.g. the missing possibility of a claim for damages.